Exploring Students’ Perceptions of Storytelling As A Strategy For Enhancing Speaking Skills - Lubis, Asmaul Husna; Lubis, Rica Umrina; Siregar, Ayu Meita Puteri (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study investigates students’ perceptions of the use of storytelling as a technique to improve speaking ability in English. The research was conducted with 22 students of the English Education Study Program at STAIN Mandailing Natal during the fifth semester. Data were collected through a questionnaire (8 closed-ended) and semi-structured interviews. The findings reveal that students perceived storytelling as an effective strategy to enhance fluency, vocabulary mastery, confidence, and communicative competence in everyday situations. Storytelling also increased classroom engagement and motivation. Furthermore, the interview data demonstrated that storytelling encouraged students to express opinions more easily and confidently, reduced speaking anxiety, and facilitated vocabulary retention. The study concludes that storytelling is not only an enjoyable and creative method but also a pedagogically significant technique that can bridge classroom learning with real-life communication.